ImQET - Objective Stereoscopic Image Quality Evaluation Tool - Cardoso, José Vinícius de Miranda; Regis, Carlos Danilo Miranda; Alencar, Marcelo Sampaio de (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2014: Proceedings of the 20th Brazilian Symposium on Multimedia and the Web, 2014)
This paper describes an application for full-reference stereoscopic image quality assessment called ImQET. The application was developed using Mono framework and C# programming language. ImQET is independent of platform and provides a friendly Graphical User Interface (GUI). The stereoscopic image signals used in the application are based in a two-view model. ImQET has objective image quality algorithms such as PSNR, SSIM, and PW-SSIM and also incorporates a recently published technique for stereoscopic image quality assessment called Disparity Weighting (DW). Numerical results corresponding to the performance of the objective measurements, which were obtained using the proposed application, are presented. ImQET can be used by academia and industry for standardization and development of objective algorithms and evaluation of impairments in stereoscopic image signals caused by processing techniques.